PENERAPAN MEDIA FLASH CARD DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA : THE APPLICATION OF FLASH CARD MEDIA IN IMPROVING STUDENTS' DESCRIPTIVE ESSAY WRITING SKILLS - Wahyu Kurniasari (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
This study aims to analyze the effectiveness of Flash Card media in improving descriptive writing skills in fourth-grade students at MI Yaspi VII Sumbersari in the 2022/2023 academic year. The study used a descriptive qualitative method with data collection through participatory observation, in-depth interviews with teachers, and analysis of student work documentation. The results showed that Flash Card media successfully increased students' interest, activeness, and enthusiasm in the learning process. Students were able to develop ideas, organize content, and enrich vocabulary based on the visual stimuli presented. However, the study also identified ongoing challenges in the technical aspects of writing, namely the use of spelling, punctuation, and the selection of appropriate diction. Overall, it can be concluded that Flash Cards are an effective learning medium for building the foundation of descriptive writing skills at the elementary school level, with the note that it needs to be accompanied by a more systematic in-depth study of linguistic aspects.